2000
DOI: 10.1083/jcb.148.3.405
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Centrin 3 in Centrosome Reproduction

Abstract: Centrosome reproduction by duplication is essential for the bipolarity of cell division, but the molecular basis of this process is still unknown. Mutations in Saccharomyces cerevisiae CDC31 gene prevent the duplication of the spindle pole body (SPB). The product of this gene belongs to the calmodulin super-family and is concentrated at the half bridge of the SPB. We present a functional analysis of HsCEN3, a human centrin gene closely related to the CDC31 gene. Tran- sient overexpression of wild-type or mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 45 publications
(59 reference statements)
2
80
1
Order By: Relevance
“…1A, left panel). As shown previously by others (54,55), tubulin and centrin staining along the length of these structures confirms that these are in fact microtubule-based, elongated centrioles.…”
Section: Overexpression Of Centrobin Results In Abnormal Long Centrisupporting
confidence: 57%
“…1A, left panel). As shown previously by others (54,55), tubulin and centrin staining along the length of these structures confirms that these are in fact microtubule-based, elongated centrioles.…”
Section: Overexpression Of Centrobin Results In Abnormal Long Centrisupporting
confidence: 57%
“…Although a recent study showed Ca 2ϩ -independent binding of centrin to a target protein (50), in most cases the activation of centrins by Ca 2ϩ is necessary for the interaction with their binding partners (16,18). In the yeast Saccharomyces cerevisiae, Ca 2ϩ facilitates binding of Cdc31p, the yeast centrin homologue, and of the human centrin isoforms 1 and 2 to Kar1p, which is necessary for division of the yeast cell (48,51,52). In our previous centrin blot overlay assays, the binding of recombinant MmCen1 to all detected interacting proteins was Ca 2ϩ -dependent (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The three centrin proteins that are expressed in human cells (30,31) display differential tissue-specific levels (27,36,49). However, all three isoforms share the key structural features that are present in EF-hand proteins (32).…”
mentioning
confidence: 99%
“…The SPB is a proteinaceous structure that is embedded in the nuclear envelope, and its duplication marks exit from the G 1 phase and the onset of chromosome duplication. The composition of the SPB has been defined, and the steps that lead to its duplication have been studied extensively using biochemical, genetic, and microscopic methods (3,5,6,18,24,28,30,43,44). An important component of the SPB is Cdc31 (3, 13), which in yeast is encoded by the essential CDC31 gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation